2000
DOI: 10.1076/0271-3683(200001)2011-hft025
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2, Bax, and c-Fos expression correlates to RPE cell apoptosis induced by UV-light and daunorubicin

Abstract: A significant protection against apoptosis of RPE cells grown on ECM compared to cells grown on uncoated plastic dishes was found after exposure to UV-A or DNR. This protection was found to be proportionally correlated to the anti-apoptotic protein Bcl-2 and inversely correlated to the expression of Bax. Furthermore a sustained induction and expression of c-Fos was found to correlate to a higher percentage of apoptotic cells of RPE cells grown on plastic. These findings demonstrate that ECM is of great importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In fact, expression of pro-and antiapoptotic Bcl-2 family proteins is altered by oxidative stress, and these proteins represent a major factor, insofar as the outcome of the apoptotic signaling, because cell survival reflects the predominance of one set of proteins over the other. In the RPE and retina, oxidative stress, increased by several factors including light exposure or reactive oxygen species, shifts the balance of Bcl-2 family protein expression toward those that favor cell damage (44,45). Because our results show oxidative-stress-induced changes in the expression of Bcl-2 proteins, they imply that the early RPE response to oxidative stress includes transcriptional, translational, and͞or posttranslational events upstream of the mitochondrial apoptotic step.…”
Section: Discussionmentioning
confidence: 57%
“…In fact, expression of pro-and antiapoptotic Bcl-2 family proteins is altered by oxidative stress, and these proteins represent a major factor, insofar as the outcome of the apoptotic signaling, because cell survival reflects the predominance of one set of proteins over the other. In the RPE and retina, oxidative stress, increased by several factors including light exposure or reactive oxygen species, shifts the balance of Bcl-2 family protein expression toward those that favor cell damage (44,45). Because our results show oxidative-stress-induced changes in the expression of Bcl-2 proteins, they imply that the early RPE response to oxidative stress includes transcriptional, translational, and͞or posttranslational events upstream of the mitochondrial apoptotic step.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, it could be demonstrated that nitric oxide protects keratinocytes and endothelial cells from UVA-induced apoptosis, probably via upregulation of Bcl-2 (56). Similarly, extracellular matrixmediated protection of retinal pigment epithelial cells from UVA-induced apoptosis was found to correlate with Bcl-2 protein expression (57). In addition, skin explants from Bcl-2 deficient mice exhibited a higher number of SC following exposure to UVB (58).…”
Section: Participation Of the Bcl-2 Protein Family And Mitochondrial mentioning
confidence: 85%
“…Studies from our laboratory indicate that treatment of MCF-7 cells with NCS results in downregulated expression of Bcl-2 and up-regulated expression of its proapoptotic analog, Bax (Liang et al, 2001). The resulting decrease in the Bcl-2/Bax ratio has been shown in other systems to trigger the release of cytochrome c from the mitochondria (Nakatsuka et al, 2000), and to thereby induce apoptosis (Putcha et al, 1999;Liang et al, 2000). Modulation of the Bcl-2/Bax ratio perhaps represents an alternative mechanism of potentiation of apoptosis in cells lacking caspase 3.…”
Section: Discussionmentioning
confidence: 99%